2013
DOI: 10.1021/mz400413v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependence of Polymer Chain Mobility within Multilayer Films

Abstract: Fluorescence recovery after photobleaching has been applied to determine, to our knowledge for the first time, the molecular weight (M w) dependence of lateral diffusion of polymer chains within layer-by-layer (LbL) films. As shown by neutron reflectometry, polyelectrolyte multilayers containing polymethacrylic acid (PMAA, M w/M n < 1.05) of various molecular weights assembled from solutions of low ionic strengths at pH 4.5, where film growth was linear, showed similar diffusion of PMAA in the direction perpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 32 publications
3
80
2
Order By: Relevance
“…It was found electrostatic LBL films can be smoothed via a brief annealing in high salt concentration solutions . Besides ionic strength, chain mobility in electrostatic LBL films may also be affected by solution pH, type of salt, temperature, charge density, and molecular weight of the polyelectrolytes . Rubner et al found a brief immersion of PAA/poly(allylamine) (PAH) films in acidic solution results in a substantial and irreversible transformation of the film morphology.…”
Section: Dynamic Properties Of Dynamic Lbl Filmsmentioning
confidence: 99%
“…It was found electrostatic LBL films can be smoothed via a brief annealing in high salt concentration solutions . Besides ionic strength, chain mobility in electrostatic LBL films may also be affected by solution pH, type of salt, temperature, charge density, and molecular weight of the polyelectrolytes . Rubner et al found a brief immersion of PAA/poly(allylamine) (PAH) films in acidic solution results in a substantial and irreversible transformation of the film morphology.…”
Section: Dynamic Properties Of Dynamic Lbl Filmsmentioning
confidence: 99%
“…This cross-shell diffusion, however, is severely hampered after the formation of asolid shell, as the polyelectrolytes not only experience the steric hindrance from the porous shell but are also subjected to attractive electrostatic interactions. [12] Consequently,the shell thickness of the microcapsules is nearly independent of the concentration of the polyelectrolytes.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This independence of the shell thickness on polyelectrolyte concentration is consistent with previous reports on PE microcapsules fabricated using water-in-oil emulsions as templates, [5a] but in striking contrast to microcapsules generated by conventional double-emulsion templating methods,i nw hich the shell is formed by chemically crosslinking polymers and the shell thickness increases with the polymer concentration. [12] Consequently,the shell thickness of the microcapsules is nearly independent of the concentration of the polyelectrolytes. This cross-shell diffusion, however, is severely hampered after the formation of asolid shell, as the polyelectrolytes not only experience the steric hindrance from the porous shell but are also subjected to attractive electrostatic interactions.…”
mentioning
confidence: 99%
“…The lack of backpack release may originate from the increased diffusion of PAH through the film, since low molecular weight polymers tend to diffuse more quickly through multilayers than higher molecular weight polymers. 42,43 Reproducibility of the releasable backpacks was tested with films assembled using BSM from another provider (Calbiochem), to account for variations between mucin sources. A solution of 100 mM melibiose in PBS triggered release for an 80 BL film from this BSM provider, demonstrating that this methodology is applicable to various mucin sources ( Figure S5).…”
Section: 2 (Bsm/jac) Films Withstand Ph and Ionic Strength Variatiomentioning
confidence: 99%